Abnormalities in Gut Microbiota and Metabolism in Patients With Chronic Spontaneous Urticaria - Wang, Xin; Yi, Wanyu; He, Liting; Luo, Shuaihantian; Wang, Jiaqi; Jiang, Li; Long, Hai; Zhao, Ming; Lu, Qianjin (Frontiers in Immunology, 2021)
Background Increasing evidence suggests that the gut microbiome plays a role in the pathogenesis of allergy and autoimmunity. The association between abnormalities in the gut microbiota and chronic spontaneous urticaria (CSU) remains largely undefined. Methods Fecal samples were obtained from 39 patients with CSU and 40 healthy controls (HCs). 16S ribosomal RNA (rRNA) gene sequencing (39 patients with CSU and 40 HCs) and untargeted metabolomics (12 patients with CSU and 12 HCs) were performed to analyze the compositional and metabolic alterations of the gut microbiome in CSU patients and HCs. Results The 16S rRNA gene sequencing results showed a significant difference in the β-diversity of the gut microbiota, presented as the Jaccard distance, between CSU patients and HCs. No significant differences were found in the α-diversity of the gut microbiota between patients and HCs. At the phylum level, the major bacteria in the gut microbiome of patients with CSU were Firmicutes, Bacteroidetes, Proteobacteria, and Actinobacteria. At the genus level, Lactobacillus, Turicibacter, and Lachnobacterium were significantly increased and Phascolarctobacterium was decreased in patients with CSU. PICRUSt and correlation analysis indicated that Lactobacillus, Turicibacter, and Phascolarctobacterium were positively related to G protein-coupled receptors. Metabolomic analysis showed that α-mangostin and glycyrrhizic acid were upregulated and that 3-indolepropionic acid, xanthine, and isobutyric acid were downregulated in patients with CSU. Correlation analysis between the intestinal microbiota and metabolites suggested that there was a positive correlation between Lachnobacterium and α-mangostin. Conclusions This study suggests that disturbances in the gut microbiome composition and metabolites and their crosstalk or interaction may participate in the pathogenesis of CSU.